THE EFFECT OF NITRATE IN DRINKING WATER ON THE LIVER FUNCTION IN LAYING HENS - A. Abdul-Razzaq, H. (The Iraqi Journal of Veterinary Medicine, 1992)
Twenty weeks old Euribrid-Hisex Brown laying hens were used to study the effect of water pollution with nitrate on the liver function in these animals. Nitrate treatment caused an increase in total serum albumin and decreased total serum globulin and cholesterol. The activity of serum GOT and GPT enzymes were not affected by the treatment with nitrate. The results indicate that nitrate did not seem to have a negative influence on the liver function, but, it appears that nitrate might depress the immune system in these animals particularly during the early stages of exposure to the pollution. The results also indicate that laying hens are capable of adapting to high doses of nitrate in drinking water.